7,8-dimethoxycoumarin Attenuates the Expression of IL-6, IL-8, and CCL2/MCP-1 in TNF-α-Treated HaCaT Cells by Potentially Targeting the NF-κB and MAPK Pathways - Nari Lee; You Chul Chung; Choon Il Kang; Sung-Min Park; Chang-Gu Hyun (Cosmetics, 2019)
7,8-dimethoxycoumarin (DMC, C11H10O4), a natural coumarin compound, is present in Citrus plants including Citrus decumana and grapefruit. It is known to have protective effects on the kidneys against Cisplatin and ischemia-reperfusion injury. However, the underlying mechanisms of its inhibitory effects on skin inflammation have not been investigated in vitro. Tumor necrosis factor (TNF)-α is known to be one of the main causative agents of skin inflammation. It induces pro-inflammatory cytokines and chemokines by activating nuclear factor-κB (NF-κB) and mitogen-activated protein kinase (MAPK) signaling. In this study, we investigated the inhibitory effect of DMC on the expression of pro-inflammatory cytokines and chemokines in TNF-α-treated human keratinocyte HaCaT cells. Pretreatment with DMC inhibited TNF-α-treated cytokines (interleukin 6; IL-6) and chemokines (IL-8 and monocyte chemoattractant protein-1). In addition, DMC significantly inhibited TNF-α-treated NF-κB activation and phosphorylation of MAPKs, such as c-Jun N-terminal kinases (JNK) and extracellular-signal-regulated kinase (ERK). These results suggest that DMC may elicit an anti-inflammatory response by suppressing TNF-α-treated activation of NF-κB and MAPK pathways in keratinocytes. Hence, it might be a useful therapeutic drug against skin inflammatory diseases.